(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Clowns have long attracted the attention of academic research, accumulating a relevant and diverse specialized literature. This article focuses on the teaching of clowning and, more specifically, on how renowned artists became trainers. We interviewed seven professionals, active in the five regions of the country, national references in artistic work and training, as highlighted by their peers. The multiplicity of teaching processes and paths taken to become masters was recurrently narrated. Different motivations, difficulties and anxieties are reported, aiming to broaden the debates about the initiation of new trainers.